Book Review: Geopiracy: Oaxaca, Militant Empiricism, and Geographical Thought. Issue 3 (November 2014) - Finn, John C.; Barnes, Trevor J.; Sheppard, Eric; Mollett, Sharlene; Bryan, Joe; Gilbert, Emily; Wood, Denis; Mitchell, Don
This book review symposium interrogates Joel Wainwright's recent text Geopiracy: Oaxaca, Militant Empiricism, and Geographical Thought (Palgrave Macillan 2013). Overtly, this text is a scathing critique of the Bowman Expeditions, launched in 2006 with several million dollars of funding from the Foreign Military Study Office (FMSO) of the US Army. Two years later, and well into the first expedition in Oaxaca, Mexico, several groups from Oaxaca responded, accusing the Bowman Expedition of "Geopiracy" and of tricking the indigenous communities involved. In mounting a robust critique of the Bowman Expeditions, in this text Wainwright simultaneously takes on several other pressing issues in the discipline of geography, among them the militarization of geography, power, ethics, transparency and consent in fieldwork, the supposed objectivity and value-less-ness of mapping, and the tepid response to the Bowman controversy mustered by the AAG. In this review symposium a diverse group of geographers respond both to the controversy as a whole, and to Wainwright's reading and critique of it. Finally, Wain-wright concludes this symposium with his response to these reviews.